RETHINKING VISIBILITY, PERSONALIZATION AND REPRESENTATION: DISABILITY ACTIVISM IN SOCIAL MEDIA - Bitman, Nomy (AoIR Selected Papers of Internet Research, 2021)
Social media enable marginalized activists to create alternative narratives that challenge mainstream discourse through personal storytelling, a performance that emphasizes personalization and visibility. Disabled activists, however, struggle in creating their online counter-narrative due to inability to conform with able-bodied notions of activism. These notions mark online disability activism as separated from able-bodied activism, ignoring the individual considerations of disabled activists. This paper addresses these gaps by presenting the individual decision-making process of users with concealable communicative disabilities regarding activist performance of disability in social media. The three stages of this process were raised during a thematic analysis of 31 in-depth interviews with autistics, stutterers and hard of hearing users, of whom seven also kept social media diaries. First, interviewees had different perceptions of disability activism in social media. These perceptions mirror the inseparable connection between a person’s self-perception as dis/abled, and one’s perceived risk of performing a disabled identity in public, which differed between experienced activists and other interviewees. Second, the interviewees’ motivations manifested their risk-benefit calculations regarding public disability exposure for the potential benefit of other disabled people, and the different forms of ’private’ disability activism in social media. Third, the design of the activist performances was influenced by interviewees’ constant awareness of the presence of their offline acquaintances on social media, and by seeing disability as a social, rather than political, issue. This three-staged process demonstrates personalization, visibility and representation not only as essential to social media activism, but also as conflictual for activists with concealable communicative disabilities.